Sociodemographic and drug prescription pattern in patients with rheumatoid arthritis in a tertiary care teaching hospital - Kairi, Vijoy Sankar; Barman, Sarajita (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Rheumatoid arthritis (RA) is a chronic systemic autoimmune inflammatory disease that affects mainly the small joints of the hands and feet. RA is widely prevalent throughout the world. Methods: A prospective and observational study was carried out on 44 patients for 6 months. Patients of either sex, aged between 18 to 70 years diagnosed with rheumatoid arthritis were screened and recruited in the study. Patients were diagnosed on the basis of clinical assessment and the lab parameters assessed were rheumatoid factor and anti-CCP (anti-cyclic citrullinated peptide antibody). Prescriptions were analyzed for socio-demographic details and drug prescribing pattern. Results: Out of 44 patients, 36 (81.82%) were females, 8 (18.18%) were males. Maximum occurred 19 (43.18) between 31 to 40 years of age. Out of 19 (43.18%), females were 16 (36.36%), males were 3 (6.83%). 39 (88.63%) were from rural and 5 (11.37%) from urban area, 21 (47.73%) illiterate, 15 (34.09%) primary educated, 7 (15.91%) secondary educated, 1 (2.27%) educated above higher secondary, 4 (9.08%) unemployed, 2 (4.55%) students, 19 (43.18%) housewives, 7 (15.91%) agricultural workers, 7 (15.91%) non-agricultural outdoor workers and 5 (11.37%) non-agricultural indoor workers. Most common co-morbidity was hypertension 28 (63.63%). Anti-CCP was positive in 38 (86.36%). All of the patients 44 (100%) received disease-modifying anti-rheumatic drugs (DMARDs). Majority of the patients were prescribed with triple DMARDs combination 30 (68.18%). Conclusions: We observed that female were dominant over the male with male: female ratio of 1: 4.5. Prescriptions pattern was primarily based on DMARDs.